Environmental health inequities at COVID-19 pandemic times: challenges and perspectives (Research, Society and Development, 2022)
Negative impacts of the COVID-19 pandemic appear to disproportionately affect different population groups by outweighing the risks in socially and environmentally marginalized segments of society. The aim of the current study is to review on how environmental health inequities have negatively impacted the fight against the COVID-19 pandemic, as well as on challenges and perspectives in the post-pandemic transition context. The saturation of health services at tertiary level, difficulties in getting access to treatment for chronic morbidities, as well as the centuries-old unequal supply of essential environmental sanitation services are determining factors for inequity and pandemic severity levels. Strategies used to minimize disparities in the access to healthcare services have been directed towards integrating primary healthcare services to the health surveillance sector, as well as further developing digital health actions. It is possible concluding that the multidimensionality of the pandemic crisis must be understood based on the socio-environmental systemic perspective, with emphasis on its potential to worsen pre-existing environmental health inequities and to produce new inequities in the future in regions and populations affected by health and environmental vulnerability.